2022
DOI: 10.15244/pjoes/143295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Air Pollution Sources and Temporal Assessment of Air Quality at a Sector in Mosul City Using Principal Component Analysis

Abstract: This study was carried out to apply principal component analysis (PCA) as a tool to identify the major sources responsible stand behind air pollution variation in a sector of Mosul city for the first time. In addition, Besides, PCA was used to construct a temporal overall air quality assessment index to find the period of best air quality along the year. The data was collected through a monitoring station located in the public library on a side of a very crowded highway and near a traffic light intersection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Before conducting further analysis, preliminary assessments are required to ensure that the dataset is sufficient for analysis [25,26]. Additionally, Bartlett's test evaluates whether the variables in a dataset are significantly correlated (p≤0.05), while the KMO test assesses the sampling adequacy, and requires value equal to or greater than 0.5 to confirm that the dataset is sufficient for further analysis.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
See 2 more Smart Citations
“…Before conducting further analysis, preliminary assessments are required to ensure that the dataset is sufficient for analysis [25,26]. Additionally, Bartlett's test evaluates whether the variables in a dataset are significantly correlated (p≤0.05), while the KMO test assesses the sampling adequacy, and requires value equal to or greater than 0.5 to confirm that the dataset is sufficient for further analysis.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…A p-value <0.0001 for Bartlett's test as shown in Table 5 justifies the acceptance of the Ha hypothesis while the result for the KMO test in Table 6 indicates adequacy with a value of 0.614. Therefore, it can be concluded that the variables are correlated, and the sampling is adequate for analysis (Bartlett, 1954;Shihab, 2022).…”
Section: Identification Source Of Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Z ij = a i1 x 1j + a i2 x 2j + a i3 x 3j + ... + a im x mj (1) where Z is the component score, a is the component loading, x is the measured value of the variable, i is the component number, j is the sample number, and m is the total number of variables (Isiyaka & Azid, 2015;Shihab, 2022).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…By analyzing the concentration of pollutants during COVID-19 lockdown and prelockdown periods, this study sought to determine the impact of COVID-19 lockdown on air quality in Hyderabad, India (Allu et al, 2021). Shihab (2022) has applied the principal component analysis (PCA) as a tool to determine the main causes underlying variations in air pollution in a part of the Iraqi metropolis of Mosul, where a temporal overall air standard evaluation index was created using PCA to determine when the air quality was at its best throughout the year. The information was gathered using a substation housed in a public library close to a traffic light intersection and an extremely congested motorway in Mosul city.…”
Section: Introductionmentioning
confidence: 99%